Retention or loss of v-mil sequences after propagation of MH2 virus in vivo or in vitro. - Biegalke, B (1987)
During propagation of the defective avian retrovirus MH2 in the presence of replication-competent helper virus, deletion of portions of the viral genome occurred frequently. After transformation of quail cells in vitro, v-mil sequences were lost, leading to populations of MH2 viruses which were highly deficient for mil gene expression but which could transform macrophage and fibroblast cells in vitro with high efficiency. In contrast, after induction of tumors in quail with mil-deficient MH2 viral stocks, a majority of the tumor DNAs contained mil+ proviruses, suggesting that there is selection for retention of the v-mil gene in vivo and that the mil protein may play a role in the oncogenicity of MH2 virus. We also isolated MH2-transformed cell lines which contained deleted proviruses arising from packaging and subsequent integration of the subgenomic v-myc-encoding mRNA. Some of these cell lines produced viruses which encoded abnormal v-myc proteins and had altered in vitro transforming properties. These altered phenotypes may be caused by mutations within the v-myc gene.